Perennial Peanut: A Quick Reference - Yoana C. Newman; Cheryl L. Mackowiak; Ann R. Blount; Jason Ferrell (EDIS)
SS-AGR-319, a 3-page illustrated fact sheet by Yoana C. Newman, Cheryl L. Mackowiak, Ann R. Blount, and Jason Ferrell, summarizes key information about the use of this forage legume in Florida. Includes additional sources of information. Published by the UF Department of Agronomy, March 2009.